CT and MR imaging findings of systemic complications occurring during pregnancy and puerperal period, adversely affected by natural changes - Yuki Himoto; Aki Kido; Yusaku Moribata; Toshihide Yamaoka; Ryosuke Okumura; Kaori Togashi (European Journal of Radiology Open, 2015)
Dynamic physiological and anatomical changes for delivery may adversely induce various specific non-obstetric complications during pregnancy and puerperal period. These complications can be fatal to both the mother and the fetus, thus a precise and early diagnosis ensued by an early treatment is essential. Along with ultrasonography, computed tomography (CT) and magnetic resonance imaging (MRI) have assumed an increasing role in the diagnosis. This article aims to discuss the pathophysiology of these complications, the indications for CT and MRI, and the imaging findings.